Effect of genotype on adipose tissue fatty acids profile of two autochthonous sheep breed - MIŠČEVIĆ, B.; RAŠKOVIĆ, Š.; GAJIĆ, D.; PUVAČA, N.; KÖNYVES, T.; STOJŠIN, M.; BURSIĆ, V.; PUHAČA, D.; GIANENNAS, I.; LJUBOJEVIĆ PELIĆ, D.; VUKOVIĆ, G. (Journal of the Hellenic Veterinary Medical Society, 2020)
This research aimed to investigate the influence of different sheep genotype on the fatty acid profile of fatty tissue. Three months old lambs of Somborska cigaja (SC) breed and Čokanska cigaja (ČC) breed, the two different genotypes of autochthonous sheep, were used in the experiment. The fatty acid composition was determined in lambs adipose tissue samples. A total of sixty 24-week-old lambs were reared under standard productive conditions fed with compound concentrate feed and dried grass 5 weeks. Fatty acid profile analysis of lambs adipose tissue was performed on capillary gas chromatography with an FI detector. Total values of saturated fatty acids in the lambs adipose tissue ranged from 53.70% (SC) to 54.87% (ČC) with a statistically significant difference (P < 0.05). In our research C18:1 fatty acid with cis-Δ9 configuration show significant differences (P < 0.05) between these two genotypes of lambs. Results of total PUFAs in our study indicate the significant influence of genotype (P < 0.05) adipose fatty acid profile of investigated two autochthonous sheep breeds. The recorded concentration of total PUFAs in SC amounted to 6.15%, while in ČC that amount was 4.69% with a significant difference, respectively. The obtained ratio of total n-6/n-3 fatty acids of 1.79 (SC), is highly lower compared to 21.33 obtained from ČC breed. According to obtain results, from the healthier aspect of consumer life, and decrease the incidence of possible inflammatory processes and disease, we would be recommended meat from Sobmorska cigaja as meat with better fatty acids profile.